2006
DOI: 10.1016/s0004-9514(06)70027-7
|View full text |Cite
|
Sign up to set email alerts
|

A six-month, supervised, aerobic and resistance exercise program improves self-efficacy in people with human immunodeficiency virus: A randomised controlled trial

Abstract: The findings of this study add to the known benefits of exercise for the HIV-infected population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
145
1
31

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(185 citation statements)
references
References 25 publications
8
145
1
31
Order By: Relevance
“…This finding is consistent with previous research documenting that inconsistent or no PA is associated with concurrent risk for NCI in HIV-infected adults [36,37]. As would be expected, HIV-infected persons had worse neurocognitive function overall.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with previous research documenting that inconsistent or no PA is associated with concurrent risk for NCI in HIV-infected adults [36,37]. As would be expected, HIV-infected persons had worse neurocognitive function overall.…”
Section: Discussionsupporting
confidence: 92%
“…The relatively limited research on PA and cognition among those living with HIV is consistent with what has been shown among HIV-uninfected adults; higher levels of PA are associated with decreased concurrent risk for NCI [36][37][38]. Moreover, work by our group among older adults living with HIV has shown that active lifestyles (including PA) are associated with better cognition and that PA is associated with better cognition and everyday functioning among older adults living with HIV [39,40].…”
supporting
confidence: 78%
“…Particularmente no que tange ao efeito da prática de atividades físicas na qualidade de vida de PVH, a população avaliada no SEAP apresentava características muito distintas das de pacientes relatados em estudos prévios sobre o tema (Baigis et al, 2002;Fillipas et al, 2006;Maharaj et al, 2011;Ogalha et al, 2011;Jaggers et al, 2016). Ao lado disso, os instrumentos para aferição da qualidade de vida variaram nos diferentes estudos, tendo sido empregados os questionários MOS-HIV (Baigis et al, 2002;Fillipas et al, 2006; e o SF-36 (Maharaj et al, 2011;Ogalha et al, 2011 Alex Florindo e Sandra Maria Lima Ribeiro, que participaram do planejamento e da aferição de desfechos da intervenção proposta no estudo.…”
Section: Aptidão Cardiorrespiratóriaunclassified
“…Ao lado disso, os instrumentos para aferição da qualidade de vida variaram nos diferentes estudos, tendo sido empregados os questionários MOS-HIV (Baigis et al, 2002;Fillipas et al, 2006; e o SF-36 (Maharaj et al, 2011;Ogalha et al, 2011 Alex Florindo e Sandra Maria Lima Ribeiro, que participaram do planejamento e da aferição de desfechos da intervenção proposta no estudo.…”
Section: Aptidão Cardiorrespiratóriaunclassified
See 1 more Smart Citation